ANALISIS KEBUTUHAN UNTUK MENINGKATKAN KEMAMPUAN TENAGA KEPENDIDIKAN DALAM MENERAPKAN PENGUASAAN PRIBADI - Puspitasari, Citra Dewie (Perspektif Ilmu Pendidikan, 2013)
The research is aimed to identify the needs for teacher’s personal mastery at SMA Negeri 111 Jakarta, from tracing the gap, the gap factor, to select a range of interventions that made it possible to develop personal mastery. Needs assessment adapted Mager and Pipe model (1970) and Rosset’s performance analysis model (2009). The research was conducted at SMA Negeri 111 Jakarta from April through Mei 202, using sampling purposive. All active teachers, the Principal, and representatives of SMA Negeri 111 Jakarta second-grade students were sample. Data was gathered by using questionnaires and interviews. Questionnaires were analyzed by descriptive statistical methods, while the interviews through data reduction, data presentation, and conclusion. The result revealed that there were gaps on the dimension of self-awareness, perceptual acuity, emotional mastery, flexibility and adaptability, autonomy, and creative resourcefulness.